Rapid Submillimeter Brightenings Associated with a Large Solar Flare - Kaufmann, Pierre (2001)
We present high time resolution observations of Active Region 8910 obtained simultaneously at 212 and 405 GHz during a large Hα flare, which produced a soft X-ray class X1.1 event. Data were obtained with the new solar submillimeter telescope recently installed at the El Leoncito Observatory to explore this poorly known part of the solar emission spectrum. A small slow submillimeter enhancement (≤300 sfu) was associated to bulk emissions at X-rays, Hα, and microwaves. The event exhibited numerous submillimeter-wave 100-300 ms duration spikes, the larger ones with fluxes on the order of 220 and 500 sfu (±20%) at 212 and 405 GHz, respectively. A dramatic increase in the incidence rate of submillimeter spikes sets in as a new large loop system appears in AR 8910, and X-ray emission increases nearly 1 hr before the large flare. The brightening incidence rate (~20 per minute) correlates well with the large flare light curves at X-rays and Hα. The submillimeter spikes may be associated to microflares, waves, or quakes in flaring active regions.